Embryonic heat conditioning induces paternal heredity of immunological cross- tolerance: coordinative role of CpG DNA methylation and miR-200a regulation - Ravi, Padma Malini; Kisliouk, Tatiana; Druyan, Shelly; Haron, Amit; Cline, Mark A.; Gilbert, Elizabeth R.; Meiri, Noam (Frontiers in Immunology, 2025)
BackgroundEnhancing an organism’s survival hinges on the development of balanced and adaptable stress response systems. While the initial stress-response set-points in the hypothalamus may be genetically determined, they are further influenced by epigenetic factors during embryonic development. A debate persists regarding the heritability of such behavioral traits. The chick in ovo heat conditioning model offers a unique insight into this fundamental question, where manipulation during embryonic development can induce heat resilience and even cross-tolerance to promote immunological resilience. In this study, we conducted an analysis of thermal manipulation during embryogenesis to demonstrate paternal heredity and investigate its transmission through sperm DNA methylation in coordination with miR-200a action.ResultFirst-generation embryos underwent in ovo heat conditioning (EHC), creating a cohort of embryonic EHC and control chicks. These chicks were then subjected to an intracranial lipopolysaccharide (LPS) challenge. Conditioning rendered the chicks immune resilient, as evidenced by their fibril effect. Male offspring were raised to maturity, and their sperm was analyzed for methylome patterns, revealing significant differences between treatments, particularly in immune and development related genes. Additionally, sperm from EHC males was used for artificial insemination of naïve Cobb hens, resulting in untreated offspring that displayed immune resilience upon LPS challenge, indicating transgenerational effects. Overlap analysis of sperm methylome and differentially methylated sites (DMS) of offspring hypothalamus revealed inheritance of altered methylation associated with specific genes. Several of these genes are potential effectors of miR-200a, whose expression profile in the hypothalamus during LPS challenge was conserved across both generations. To evaluate the role of miR-200a in cross-tolerance acquisition, miR-200a was intracranially injected, and RNA-seq analysis of the hypothalamus revealed genes involved in the regulation of developmental and metabolic processes, stress, and immune response.ConclusionThis study demonstrates paternal trait heredity by revealing that EHC induces cross-tolerance with the immunological system, rendering chicks resilient to LPS that transgenerationally transmit this to untreated offspring. Additionally, analysis of sperm methylation patterns in EHC mature chicks led to identification of genes associated with neuronal development and immune response, indicating potential neural network reorganization. Finally, miR-200a emerges as a regulator potentially involved in mediating the cross-tolerance effect.